2007
DOI: 10.1159/000112497
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Endotoxin Enhance Allergen-Stimulated Proliferation and Reduce the Threshold for Activation in Human Peripheral Blood Cells

Abstract: Background: Endotoxins, comprised of bacterial cell wall lipopolysaccharides (LPS), have been reported to have both protective and exacerbating effects on the development and maintenance of allergic disease in humans and on markers of allergic inflammation in animal models of allergy. In this study, we investigated the effect of low concentrations of LPS on human peripheral blood mononuclear cells (PBMC) stimulated with the major cat allergen Fel d 1. Methods: Extensive purification of recombinant (r) Fel d 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Additional cytokine analysis (IL-6, IL-10, IL-17A, IFN-γ, and TNF) was performed with CBA, but no significant differences were observed between PBMCs from cat-allergic and healthy donors cocultured with the different exosome preparations (data not shown). Similar results for IL-10 and IFNγ have been previously observed for PBMCs treated with only Fel d 1 (5).…”
Section: Resultssupporting
confidence: 88%
“…Additional cytokine analysis (IL-6, IL-10, IL-17A, IFN-γ, and TNF) was performed with CBA, but no significant differences were observed between PBMCs from cat-allergic and healthy donors cocultured with the different exosome preparations (data not shown). Similar results for IL-10 and IFNγ have been previously observed for PBMCs treated with only Fel d 1 (5).…”
Section: Resultssupporting
confidence: 88%
“…It is well known that at LPS concentrations lower than 1 ng/ml the system responds digitally or does not respond at all, thus representing an activation threshold 45,46 . We observed a clear non-linear activation curve (phosphorylation) in both systems of NF-κB and MAPK cascades (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such property provided the possibility for further purification of the vaccine. Moreover, amebocyte lysate analysis showed that both Der f 36 and hypoallergenic Der f 36 were almost endotoxin-free molecules according to a previous study ( 45 ), which is crucial for animal experiment and PBMC cytokine expression.…”
Section: Discussionmentioning
confidence: 73%